2003
DOI: 10.1210/en.2002-220708
|View full text |Cite
|
Sign up to set email alerts
|

The Severe Form of Hypertension Caused by the Activating S810L Mutation in the Mineralocorticoid Receptor Is Cortisone Related

Abstract: A gain of function mutation resulting in the substitution of leucine for serine at codon 810 (S810L) in the human mineralocorticoid receptor (MR) is responsible for early-onset hypertension that is exacerbated in pregnancy. All steroids, including progesterone, that display antagonist properties when bound to the wild-type MR are able to activate the mutant receptor (MR(L810)). These findings suggest that progesterone may contribute to the dramatic aggravation of hypertension in MR(L810) carriers during pregna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
54
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(57 citation statements)
references
References 13 publications
0
54
0
3
Order By: Relevance
“…Prog activation of the MR is unexpected because Prog is an antagonist for wild-type human MR (Kagawa 1958, Wambach & Higgins 1978, Funder & Adam 1981, Rupprecht et al 1993b, Geller et al 2000, Rafestin-Oblin et al 2003, Sugimoto et al 2016. The mineralocorticoid activity of Prog for Leu-810 MR explained high blood pressure in pregnant woman with this mutant MR.…”
Section: Evolution Of the Contact Between Ser810 (Helix 5) And Ala773mentioning
confidence: 99%
“…Prog activation of the MR is unexpected because Prog is an antagonist for wild-type human MR (Kagawa 1958, Wambach & Higgins 1978, Funder & Adam 1981, Rupprecht et al 1993b, Geller et al 2000, Rafestin-Oblin et al 2003, Sugimoto et al 2016. The mineralocorticoid activity of Prog for Leu-810 MR explained high blood pressure in pregnant woman with this mutant MR.…”
Section: Evolution Of the Contact Between Ser810 (Helix 5) And Ala773mentioning
confidence: 99%
“…Subsequently, Rafestin-Oblin et al 14 showed that cortisone was able to activate this mutant MR. The activation results in part from stabilization of an interaction between helix 3 and helix 5.…”
Section: Mineralocorticoid Receptormentioning
confidence: 99%
“…8,14 -16 Aldosterone-binding specificity is conferred by a region including helices 6 and 7, which do not contribute to the pocket. 14 Li et al 8 analyzed the interactions of this region with residues that contribute to the pocket; it may also be that the interaction of such regions with the hsp90 complex may be important in determining the conformation of the unliganded pocket. 15 Although none of these present studies have crystallized the MR LBD with the antagonists spironolactone or eplerenone, the analysis of Bledsoe et al 7 and indeed previous modeling 17,18 suggest that its mechanism of inactivation differs from that of RU486 in the progesterone receptor and tamoxifen/raloxifene in the estrogen receptor, where displacement of helix 12 is a major component of the antagonism.…”
Section: Mineralocorticoid Receptormentioning
confidence: 99%
“…These disorders are exemplified by mineralocorticoid excess, glucocorticoid-remedial aldosteronism, pseudohypoaldosteronism type II (PHAII), and Liddle's syndrome. They result from inactivated 11-␤-HSD2, 1 fused 11-hydroxylase/aldosterone (aldo) synthase (AS), 2 gain-of-function mutations in the mineralocorticoid receptor (MR), 3 or in the with-no-lysine (K) kinases WNK1 and WNK4 4,5 or gain-of-function mutations in ␤ and ␥ subunits of the epithelial sodium channel (ENaC), 6,7 respectively. All of these mutations impinge on salt absorptive mechanisms in the kidney.…”
mentioning
confidence: 99%